Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Rapport sur le développement humain en Afrique 2016 : accélérer les progrès en faveur de l'égalité des genres et de l'autonomisation des femmes en Afrique (PNUD, 2016)
Les disparités entre les genres coûtent quelque 95 milliards de dollars US par an en moyenne à l’Afrique subsaharienne et ont culminé à 105 milliards de dollars de pertes en 2014 (soit 6 % du PIB régional), compromettant de ce fait les efforts du continent en faveur d’un développement humain et d’une croissance économique inclusifs, indique le Rapport. Le rapport du PNUD analyse les facteurs politiques, économiques et sociaux qui entravent la promotion de la femme en Afrique et propose des politiques et des mesures concrètes pour combler l’écart entre les genres. Il s’agit notamment de corriger la contradiction entre la législation et la pratique afin de passer d’une égalité des genres juridique à une égalité de fait, de rompre avec les normes sociales préjudiciables aux femmes et de transformer les cadres institutionnels discriminatoires, en vue de garantir la participation économique, sociale et politique des femmes. D’après le rapport, une augmentation de 1 % de l’indice d’inégalité de genre contribuerait à réduire l’indice de développement humain (IDH) d’un pays de 0,75 % [...]
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; afrique; approches et analyses; autonomisation; discipline; inégalités; pauvreté; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; égalité des sexes; épistémologie

Travail-famille : un défi pour les femmes à Cotonou - Adjamagbo, Agnès; Gastineau, Bénédicte; Kpadonou, Norbert (Recherches Feministes, 2016)
En Afrique de l’Ouest, le taux d’activité des femmes est élevé. Souvent cantonnées dans le secteur informel, elles contribuent pourtant de façon importante aux revenus du ménage. Toutefois, les rôles socialement prescrits imposent aux femmes la quasi-intégralité des tâches domestiques et des soins aux enfants. Cet article étudie la manière dont les femmes actives à Cotonou, au Bénin, gèrent leur quotidien entre contraintes familiales et obligations professionnelles. L’analyse montre que la conciliation incombe à toutes les femmes, quel que soit leur milieu socioéconomique. La différence se joue plutôt dans les ressources sociales et financières dont elles disposent pour pallier le fardeau de la double journée.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; approches et analyses; bénin; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; double journée de travail; démographie; famille; inégalités; maternité; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
https://academic.oup.com/ia/article/92/5/1041/2688120
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

Leading in disadvantaged Zimbabwean school contexts: Female school heads’ experiences of emotional labour - Zikhali, Joyce; Perumal, Juliet (Educational Management Administration and Leadership, 2016)
This qualitative multiple case study explored the sources of emotional stress experienced by 12 female Zimbabwean primary heads leading in socio-economic disadvantaged schools in Masvingo District and their attempts to alleviate the challenges that the children from these disadvantaged contexts presented them with. Data was generated through individual semi-structured interviews, and observations and the data was analysed thematically to elicit the sources of their emotional labour that emanated from stress-related cultural and contextual factors. The study revealed that despite the school heads experiencing anxiety, pain, sorrow, sympathy, frustration, sadness, and concern they were happy about their appointments to leadership positions. The sources of their emotional stress were related to the plight of children; stereotypical gender expectations; lack of parental cooperation; and unrealistic professional and social expectations. The study suggests wellness recesses; the establishment of social networks through which heads could share their experiences; and professional development programmes on stress management as possible interventions that could help the heads deal with these stressful circumstances. © 2015, © The Author(s) 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; directrices d'école; enfants orphelins; environnement; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail émotionnel; zimbabwe; éducation

Chroniques d'une musulmane indignée - Ibnouzahir, Asmaa (Fides, 2015)
En plus d'un récit autobiographique racontant les défis qu'elle a relevés en tant que jeune immigrante musulmane d'origine marocaine arrivée au Québec en 1994, Asmaa Ibnouzahir présente également une analyse éclairante sur des questions qui reviennent souvent dans nos médias au sujet de l'islam, des femmes et de la société: les musulmans «modérés», les crimes «d'honneur», le foulard, le féminisme islamique et bien d'autres. Islamiste pour certains et hérétique pour d'autres, Asmaa Ibnouzahir partage avec nous son parcours personnel et militant qui a fait d'elle la citoyenne québécoise musulmane, féministe et indignée qu'elle est aujourd'hui. Engagée dans les débats sociopolitiques qui ont traversé le Québec au cours de la dernière décennie, sur la religion, l'immigration et les valeurs québécoises, Asmaa Ibnouzahir livre un témoignage essentiel qui donne un accès sans précédent aux coulisses de ces débats. Depuis une dizaine d'années, Asmaa Ibnouzahir est engagée dans la réflexion et les débats sociaux autour des droits de la personne, notamment sur les questions touchant autant à l'immigration et à la religion dans la sphère publique qu'au statut des femmes dans l'Islam. Elle a également voyagé et travaillé dans plus d'une quinzaine de pays en tant que spécialiste de la nutrition d'urgence humanitaire. – [Renaud-Bray].
Section: 367 pages ; 23 cm
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; amériques; approches et analyses; canada; com5170; corps; cours; discipline; droits des femmes*; droits des personnes; féminisme islamique; immigration; maroc; point de vue situé; premier cycle; périodes historiques; québec; religion; régions géographiques; science politique; science politique et droit; thématiques

Gender and the political economy of land in Africa - Kouamé, Euphrasie B.H.; Fofona, Namizata B. (United Nations University Institute for Natural Resources in Africa, 2015)
Evidence shows that secure land rights have positive effects on poor people in general and women in particular, especially where households previously had little security. Several countries in Africa have been undertaking land reform initiatives that prohibit gender-based discrimination; however, the results revealed a substantial gap between the development of laws and their effective implementation. This paper draws attention to the political systems within which land tenure and property rights operate, especially for women. It also points out the main challenges in securing women’s land rights in Africa and highlights the economic, social and environmental benefits of increasing women’s access to land. The analysis shows that although many of the changes in policy and law appear to be legal and technical, access to and control over land is in practice related to socio-economic characteristics and governed by cultural practices and power relations at the family, community and country levels. The paper therefore recognizes the need for innovative approaches that go beyond property rights in operationalising strategies that strengthen women’s access to land. It is not enough for land legislation to be gender-sensitive; it must be gender-transformational. Land markets could potentially contribute to this transformation but their role is still limited by poor institutional capacity. The roles that different actors (women, men, women’s organizations, community leaders, donors) can play would be crucial in the process of securing women’s access to land in Africa.
ISBN: 9789988633066
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; femmes*; genre; identités LGBTQIA2+; politique; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; égalité des sexes

Plaisirs croisés: gukuna-kunyaza. Missions, corps et sexualités dans le Rwanda contemporain - Michela Fusaschi (Genre, Sexualité et Société, 2012)
Based on ethnographic research in post-genocide Rwanda, this article analyzes how femininity is embodied through a ritual practice called gukuna, which consists of the elongation of the labia minora through a reciprocal massage between young women. This social construction of the female body, in addition to kunyaza, a traditional male sexual technique, is expected to facilitate pleasure during sexual intercourse. Through an analysis of colonial period texts as well as recent interviews, this article shows how this ritual, has persisted in the country despite its condemnation by the Catholic Church since the colonial time, and explores how it is being reinterpreted by women.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afro-féminisme; approches et analyses; corps; cours; discipline; féminisme africain; gukuna; premier cycle; périodes historiques; rituel; rwanda; régions géographiques; science politique; science politique et droit; sex2283; sexualité; thématiques

Identifications homosexuelles, construction identitaire et tensions postcoloniales entre le Cameroun et la France - Awondo, Patrick (L’Espace Politique, 2011)
L’article problématise la circulation de l’« identité homosexuelle » dans l’entre-deux de l’Occident et de l’Afrique. À partir de l’exemple camerounais, il montre comment des « tensions postcoloniales » parasitent le débat autour de l’homosexualité en se cristallisant notamment sur l’affrontement symbolique entre ordres moraux opposés. Au-delà des identifications sexuelles, l’analyse aborde aussi la situation des individus qui tentent par la migration d’échapper au régime de contrainte camerounais et se retrouvent dans la posture de « réfugié (homo)sexuel » en France, sans que pour autant la question de leur « identité » sexuelle soit « résolue ».
Keywords: 1900-1999; 1970-1979; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; afrique; approches et analyses; cameroun; cours; discipline; europe; france; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Les monologues voilés (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Place: Paris Publication Title: Scènes & Cies
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte